Phylogeography and Historical Demography of Two Sympatric Atlantic Snappers: Lutjanus analis and L. jocu - Souza, Allyson Santos de; Dias Júnior, Eurico Azevedo; Perez, Manolo Fernandez; Cioffi, Marcelo de Bello; Bertollo, Luiz Antonio Carlos; Garcia-Machado, Erik; Vallinoto, Marcelo Nazareno Souza; Pedro Manoel, Galetti; Molina, Wagner Franco (Frontiers in Marine Science, 2019)
Lutjanus analis (mutton snapper) and L. jocu (dog snapper) are mesopredator species with extensive geographic distribution in the Atlantic Ocean. Although historically overfished, their genetic diversity, population structuring, and historical demography along the Brazilian coast are unknown. Here we present genetic data for the hypervariable region 1 (HVR1) of the mtDNA control region of both L. jocu and L. analis, and for cytB of L. analis from distinct geographic regions. Phylogeographic analyses based on HVR1 sequences revealed no geographic structuring of mtDNA lineages for either species. The bimodal mismatch distribution plots of mutton and dog snapper populations implied that they might have experienced secondary contact. Historical demographic parameters estimated that population expansions ranged from 13,631 to 61,171 years before present (ybp) for L. analis and 36,783-55,577 ybp for L. jocu, associated with events that occurred at the end of the last glaciation period. Estimates of the average effective population size for L. jocu were higher than those for L. analis, with the largest population occupying the Brazilian northeastern region coast. High migration rates are maintained among the three northernmost locations, with a substantial decrease to the further southern region. Our study suggests that a tripartite interaction of larval dispersion and interregional adult movement (aggregate spawning), allied to historical contingencies, contributed to contemporary population genetic patterns of these species, and adds relevant information for conservation management of such vulnerable - and valuable - marine resources.